Proceedings of the 2nd International Conference on Internet of Things, Big Data and Security 2017
DOI: 10.5220/0006404204780481
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model to Investigate an Individual’s Behavioural Towards using Cloud Computing

Abstract: Cloud computing technology can bring benefits at both individual level and organisational level, for example, flexibility and cost saving. However, there is a lack of empirical studies that examine the usage of cloud computing technology from an individual's perspective. In fact, the adoption of cloud services in Middle Eastern counties like Saudi Arabia is still low compared with developed countries. Therefore, this study aims to investigate the end users' behavioural towards using cloud computing services in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This popularity of cloud computing technologies in libraries has been attributed to its capability of providing quicker on-demand computing infrastructures, self-service, and independent capability to access information resources (Changchit & Chuchuen, 2018). Alkhater at al. (2017) indicated that cloud computing has been among the present-day popular technologies offering IT resources as utility services.…”
Section: Page24mentioning
confidence: 99%
“…This popularity of cloud computing technologies in libraries has been attributed to its capability of providing quicker on-demand computing infrastructures, self-service, and independent capability to access information resources (Changchit & Chuchuen, 2018). Alkhater at al. (2017) indicated that cloud computing has been among the present-day popular technologies offering IT resources as utility services.…”
Section: Page24mentioning
confidence: 99%